Are the global real estate markets contagious? - C. M. Hui, Eddie; Chan, Ka Kwan Kevin (International Journal of Strategic Property Management, 2012)
The aim of this paper is to investigate the contagion across real estate markets of four countries: Hong Kong, China, U.S. and U.K., during the financial tsunami in 2008. We use the Forbes-Rigobon test, the coskewness test and the cokurtosis test. We propose a new cokurtosis test constructed by extending the method of constructing the coskewness test to further higher order moments. It can show additional channels of contagion that other tests fail to show, and hence can provide more information on the direction of contagion, and reflect a more complete picture of the contagion pattern. The coskewness and cokurtosis tests show that contagion exists between the four countries, and the contagion effect is stronger between Hong Kong and China, and between U.S. and U.K. This provides clues for investors on how to diversify their investment to reduce their risk. This paper bridges the gap that previous works on contagion across real estate markets give mixed results, and gives a first insight into the contagion pattern of global real estate markets during the financial tsunami.First Publish Online: 2 Oct 2012